IMPLEMENTASI PENGAWASAN PEMERINTAHAN PADA PENERAPAN APLIKASI SISTEM INFORMASI PEMERINTAHAN DAERAH (SIPD) DI DINAS PERDAGANGAN PROVINSI SULAWESI SELATAN - Alwany, Taufan (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2024)
The Ministry of Home Affairs has developed a Regional Government Information System (SIPD) to replace the previous system, SIMDA. The aim is to create an efficient, effective, accurate, transparent and accountable information system, connecting the central government with regional governments. Accuracy and completeness of information is the key to increasing government service capabilities, so a supporting information system is needed. This research aims to analyze the implementation of SIPD in the South Sulawesi Province Trade Service using qualitative methods. Policy implementation theory by George C. Edward III is used as a framework, which emphasizes four variables important for policy success: Communication, Resources, Attitudes or Dispositions, and Bureaucratic Structure. The research results show that there are obstacles in understanding SIPD implementers, so intensive training is needed to improve implementers' capabilities in using this system